Stimulation Techniques in Increasing Dysaudia Children's Ability to Speak Fonem Konsonan Apico Alveolar - Komaladini, Santi (Department of Special Education, 2020)
The tongue is one of the most important articulators in the language of sound. The tongue makes various sounds, both vowels, and consonants, that produce words and sentences. Children in their siblings experience an inability to hear difficulties in their auditory feedback. Hearing disability causes their articulation abilities to be very limited. Articulation is an important component of verbal communication. Articulation has a close relationship with phonology and other aspects of communication. Therefore, use the right media to help pronounce the sentence more easily stimulated when speaking, it is necessary to practice articulation for them. Sweet spatulas are made to help the tip of the tongue so that it is indeed a compilation of words containing Alveolar Apico Phonemes. The results showed an increase in children's ability to articulate words containing Alveolar Apico both in front, middle, and back of the baseline session compared to using sweet tongue spatula media. Increasing Dysaudia child's ability shows sweet taste stimulation on the tip of the tongue that can stimulate the brain, which provides the tip of the tongue for movement and movement in articulation that produces the words needed